Controversy about the certainty of knowledge - Noras, Andrzej J. (Folia Philosophica, 2010)
Review of Aleksander R. Bańka's book Désiré Merciera ogólna teoria pewności (Désiré Mercier's General Theory of Certainty), Katowice: University of Silesia Press, 2008.